PK/PD Analysis of Marbofloxacin by Monte Carlo Simulation against Mycoplasmaagalactiae in Plasma and Milk of Lactating Goats after IV, SC and SC-Long Acting Formulations Administration - Emilio Fernández-Varón; Edgar García-Romero; Juan M. Serrano-Rodríguez; Carlos M. Cárceles; Ana García-Galán; Carlos Cárceles-García; Rocío Fernández; Cristina Muñoz; Christian de la Fe (Animals, 2021)
Contagious agalactia is a mycoplasmosis affecting small ruminants that have become an important issue in many countries. However, PK/PD studies of antibiotics to treat this problem in lactating goats affected by Mycoplasma (M.) agalactiae, the main CA-causing mycoplasma are almost non-existent. The aims of this study were to evaluate the plasma and milk disposition of marbofloxacin in lactating goats after intravenous (IV), subcutaneous (SC) and subcutaneous poloxamer P407 formulations with and without carboxy-methylcellulose (SC-P407-CMC and SC-P407) administration. Marbofloxacin concentrations were analysed by the High Performance Liquid Chromatography (HPLC) method. Minimum inhibitory concentrations (MIC) of M. agalactiae field isolates from mastitic goat’s milk were used to calculate surrogate markers of efficacy. Terminal half-lives of marbofloxacin after IV, SC, SC-P407 and SC-P407-CMC administration were 7.12, 6.57, 13.92 and 12.19 h in plasma, and the half-lives of elimination of marbofloxacin in milk were 7.22, 7.16, 9.30 and 7.74 h after IV, SC, SC-P407 and SC-P407-CMC administration, respectively. Marbofloxacin penetration from the blood into the milk was extensive, with Area Under the Curve (AUCmilk/AUCplasma) ratios ranged 1.04–1.23, and maximum concentrations (Cmax-milk/Cmax-plasma) ratios ranged 0.72–1.20. The PK/PD surrogate markers of efficacy fAUC24/MIC and the Monte Carlo simulation show that marbofloxacin ratio (fAUC24/MIC > 125) using a 90% of target attainment rate (TAR) need a dose regimen between 8.4 mg/kg (SC) and 11.57 mg/kg (P407CMC) and should be adequate to treat contagious agalactia in lactating goats.